2007
DOI: 10.1039/b701684k
|View full text |Cite
|
Sign up to set email alerts
|

α-TEPHOS: a cyclodextrin-derived tetraphosphine for multiple metal binding

Abstract: The tetraphosphine 6(A),6(B),6(D),6(E)-tetradeoxy-6(A),6(B),6(D),6(E)-tetra(diphenylphosphinyl)-2(A),2(B),2(C),2(D),2(E),2(F),3(A),3(B),3(C),3(D),3(E),3(F),6(C),6(F)-tetradeca-O-methyl-alpha-cyclodextrin (alpha-TEPHOS) has been prepared in high yield by reacting 6(A),6(B),6(D),6(E)-tetra-O-methylsulfonyl-2(A),2(B),2(C),2(D), 2(E),2(F),3(A),3(B),3(C),3(D),3(E),3(F),6(C),6(F)-tetradeca-O-methyl-alpha-cyclodextrin with excess PPh(2)Li. The product was purified in its BH(3)-protected form. alpha-TEPHOS is the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In organic media, asymmetric hydrogenation of various prochiral substrates was performed by using a diphosphite-a-CD (dimethyl itaconate; ee 84 %), [4] a diphosphane-b-CD (derivatives of cinnamic acid or ester, acrylic acid or ester and itaconic acid or ester; ee 49-92 %), [24] and a tetraphoshane-a-CD (amino acid precursor, ee 25 %) as ligands. [21] A diphosphite-a-CD [4] and a monophosphinite-b-CD [3] were exploited in hydroformylation reactions of aryl and alkyl olefins. A diphosphane-a-CD was also used in an ethene and propene dimerisation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In organic media, asymmetric hydrogenation of various prochiral substrates was performed by using a diphosphite-a-CD (dimethyl itaconate; ee 84 %), [4] a diphosphane-b-CD (derivatives of cinnamic acid or ester, acrylic acid or ester and itaconic acid or ester; ee 49-92 %), [24] and a tetraphoshane-a-CD (amino acid precursor, ee 25 %) as ligands. [21] A diphosphite-a-CD [4] and a monophosphinite-b-CD [3] were exploited in hydroformylation reactions of aryl and alkyl olefins. A diphosphane-a-CD was also used in an ethene and propene dimerisation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Matt and Se´meril showed that cavity-shaped ligands could bring an added value in the efficiency of the Suzuki-Miyaura coupling. 12 Furthermore, although cavity-shaped tetraphosphines derived from calixarenes, 13 resorcinarenes 14 or cyclodextrins 15 (CDs) have been synthesized, none of them has been probed in a low-loading catalytic system to the best of our knowledge. In addition, we have shown that perbenzylated CDs regioselectively functionalized with two phosphines could serve as pseudo-enantiomeric platforms in enantioselective catalysis.…”
mentioning
confidence: 99%
“…Removal of the BH 3 protecting groups was carried out quantitatively in boiling HNEt 2 . [29] The 31 P NMR spectrum of pure diphosphane 10, recorded in C 6 D 6 , displayed two nearly identical singlets at d = À15.2 and À15.0 ppm; values that are typical of dialkylphenylphosphanes. The "introverted" character of diphosphane 10 was revealed by a Although the two non-equivalent phosphorus atoms are too far apart for significant 31 …”
Section: Resultsmentioning
confidence: 99%